RESIDENTS-TOURISTS RELATIONSHIPS - THE INFLUENCE OF THE SOCIO-DEMOGRAPHIC CHARACTERISTICS ON THE RESIDENTS’ ATTITUDE TOWARD TOURISM - Andreea-Daniela MORARU (Management & Marketing)
Tourism has witnessed an outstanding development during the last few decades and has proven its resilience and ability to recover following periods of crisis. Numerous topics related to the development of tourism have been tackled and given its impact on the tourism destination, it is only natural that particular attention has been paid to the residents-tourists relationships under their various forms of manifestation. The present paper aims at presenting the residents' perception of the impact of tourism in Constanta (Romania), a tourist city on the Black Sea coast. To this end, a descriptive research of quantitative type was performed and several hypotheses were formulated regarding the influence of a set of socio-demographic variables on the residents’ attitude toward tourism. The research revealed there were differences in the attitude toward tourism between professional groups and age groups, while gender and income did not seem to have a significant influence.